Sport Participation as A Determinant of Socio-Emotional Skill Acquisition Among Primary School Pupils - Azeez Arisekola SALMAN; Blessing Titilayo ADEOYE (Journal of Education Reseach and Evaluation, 2025)
Inconsistent integration of socio-emotional skills in elementary education hinders children’s holistic, academic, and social development. The primary objective of this study is to critically examine the extent to which sport participation can predict and enhance the acquisition of socio-emotional skills among elementary school students. This study employed a descriptive survey research design. The sample consisted of 377 students selected from a population of 21,428 students using a multi-stage sampling technique. Data were collected using two validated research instruments: the Socio-emotional Skills Acquisition Rating Scale (SESARS) and the Sport Participation Structured Rating Scale (SPSRS). Descriptive statistics (mean, percentage, and standard deviation) were used to answer the research questions, while Pearson Product–Moment Correlation (PPMC) and t-tests were applied to test the hypotheses at a 0.05 significance level. The results indicate that 98.9% of students demonstrated a high level of sport participation and 77.5% exhibited high socio-emotional skills acquisition. A significant positive relationship was found between sport participation and socio-emotional development. Additionally, significant gender differences were observed in sport participation; however, no significant gender differences were found in socio-emotional skills acquisition. The study concludes that engagement in structured sports has a measurable impact on enhancing students’ socio-emotional skills. These findings imply that schools should strengthen structured, inclusive, and gender-responsive sports programs as part of a holistic development model to promote students’ socio-emotional well-being.